KARAKTERISTIK WAJAH GURU YANG DISUKAI BERDASARKAN PERSPEKTIF MURID SEKOLAH DASAR - GUMGUM GUMELAR; MIRDAS AL-ASY 'ARY (Journal of Research and Measurement in Psychology: JPPP, 2016)
In addition to the teacher must have the quality of academic competence, quality and a good pedagogic competence also exists in non-verbal behavior components face. The characteristics of teacher's face is divided into four types: Anomalous Face, Baby Face, Emotion Face and Familiar Face. This research is descriptive research, data retrieval technique using the Likert Scale, Guttman Scale and Manipulation Cchecks for participants control never see facial characteristics of the teachers presented earlier. In data retrieval, facial characteristics of teachers compared with other teachers face characteristics. Based on the perspective of primary school students in the research sample, the result is the characteristic of the teacher's face Familiar Face menservants and characteristic facial Emotion Face female teachers have the highest value. Result shows that familiar face characteristics for male teachers and emotion face characteristics for female teachers have the highest scores.